2009
DOI: 10.1111/j.1600-9657.2008.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determining factors of traumatic injuries to primary teeth in preschool children

Abstract: The objective of the study was to assess the prevalence of dental injuries and the influence of determining factors in preschool children from Belo Horizonte, Brazil. A cross-sectional survey was carried out through clinical examinations and the application of a questionnaire to the parents of 419 children aged 0 to 5 years attending preschool. The sample was stratified by region, type of institution and age. The eighteen preschools visited were chosen randomly. The prevalence of traumatic injury to primary te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
169
8
25

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(240 citation statements)
references
References 13 publications
32
169
8
25
Order By: Relevance
“…Previous studies have demonstrated that there is a tendency for children with an incisal overjet > 3 mm and inadequate lip coverage to experience more dental injuries. [8][9] However, while the association between overjet, lip coverage, and TDI is well established, the relationship between socioeconomic factors and the occurrence of dental Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript. trauma among preschoolers is not clear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that there is a tendency for children with an incisal overjet > 3 mm and inadequate lip coverage to experience more dental injuries. [8][9] However, while the association between overjet, lip coverage, and TDI is well established, the relationship between socioeconomic factors and the occurrence of dental Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript. trauma among preschoolers is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Although several recent studies have assessed the prevalence of TDI in primary teeth and its associations with socioeconomic indicators, the results have been inconsistent and conflicting. [5][6][7][8][9][10] In Brazil, the TDI prevalence in primary teeth ranges from 9.4% to 41.6%, [5][6] and there is evidence that TDI prevalence in deciduous teeth is increasing. 9 Moreover, it is well known that the majority of TDIs involve the anterior teeth, [6][7][8] and that their appearance and position have important psychological and social impacts on children's quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the other studies also support the relationship between both risk factors and the presence of dental trauma [11][12][15][16] . Others mention that a relationship was not found or was not statistically significant in both cases 1,18 .…”
Section: Discussionmentioning
confidence: 82%
“…It was 38.3% (n = 23), which translates into a high prevalence. Various studies present wide-ranging values, from 4.15% to 44.2% 1,11,13,[15][16][17][18][19][20] . This rate varies considerably between studies, since the methodology employed in each differs significantly.…”
Section: Discussionmentioning
confidence: 99%